2019
DOI: 10.1101/698845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-genetic intra-tumor heterogeneity is a major predictor of phenotypic heterogeneity and ongoing evolutionary dynamics in lung tumors

Abstract: Impacts of genetic and non-genetic intra-tumor heterogeneity (ITH) on tumor phenotypes and evolvability remain debated. We analyzed ITH in lung squamous cell carcinoma (LUSC) at the levels of genome, transcriptome, tumor-immune interactions, and histopathological characteristics by multi-region profiling and using single-cell sequencing data. Overall, in LUSC genomic heterogeneity alone was a weak indicator of intra-tumor non-genetic heterogeneity at immune and transcriptomic levels that impacted multiple canc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…Such plasticity during metastasis can lead to phenotypic (non-genetic) heterogeneity, as witnessed in circulating tumour cells (CTCs) across cancer types (Bocci et al, 2021;Yu et al, 2013). Consistent with observed impact of plasticity on evolvability of cellular traits (Fierst, 2011), non-genetic heterogeneity has been identified to impact evolutionary dynamics in lung cancer beyond genetic heterogeneity as well (Sharma et al, 2019).…”
Section: Are Mutations Necessary For Cancer Progression?mentioning
confidence: 81%
“…Such plasticity during metastasis can lead to phenotypic (non-genetic) heterogeneity, as witnessed in circulating tumour cells (CTCs) across cancer types (Bocci et al, 2021;Yu et al, 2013). Consistent with observed impact of plasticity on evolvability of cellular traits (Fierst, 2011), non-genetic heterogeneity has been identified to impact evolutionary dynamics in lung cancer beyond genetic heterogeneity as well (Sharma et al, 2019).…”
Section: Are Mutations Necessary For Cancer Progression?mentioning
confidence: 81%
“…have not yet demonstrated disease-associated PRSS3 variants (https://www.nextprot.org/entry/NX_P35030/medical). Alternative splicing forms dynamic interactome offering precise therapeutic approaches to correcting cancer-speci c defects caused by mis-splicing regulation, in which epigenetics plays an essential role [9,11,12,49,[52][53][54]. Our previously study showed epigenetic silencing of PRSS3 in HCC [35], we reasoned epigenetic regulation of PRSS3-SVs contributing to non-genetic heterogeneity in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…While genomic heterogeneity in tumors has been extensively studied, quantifying non-genetic (i.e. phenotypic) heterogeneity has been possible only recently through investigating cell-tocell variability in isogenic populations [40][41][42][43]. Higher phenotypic heterogeneity may encourage cancer invasion [44] as well as the evolution of therapy resistance [45].…”
Section: Discussionmentioning
confidence: 99%